Stepwise Adipogenesis of Decellularized Cellular Extracellular Matrix Regulates Adipose Tissue-Derived Stem Cell Migration and Differentiation - Ziang Zhang; Rongmei Qu; Tingyu Fan; Jun Ouyang; Feng Lu; Jingxing Dai (Stem Cells International)
Microenvironmental factors can modulate the cellular status of adipose tissue-derived stem cells (ASCs). In response to microenvironmental changes, cells can remodel extracellular matrix (ECM) proteins, which play an important role in regulating cell behaviors. During adipogenic differentiation, ECM components secreted from ASCs remodel dramatically. To evaluate the role of stepwise adipogenesis-induced cellular secretion of ECM on the behavior of ASCs, we cultured ASCs in growth and adipogenic media, and ECM secreted from cells was characterized and decellularized. The ASCs were then reseeded on decellularized ECM (d-ECM) to determine the regulatory effects of ECM on cellular behaviors. During adipogenesis, cell-secreted ECM underwent remodeling characterized by conversion from fibronectin-rich ECM to laminin-rich ECM. The cellular status of ASCs was tested after reseeding on decellularized ECM. When reseeded on growth d-ECM, ASCs exhibited greater migration ability. In contrast, ASCs seeded on adipogenic d-ECM underwent adipogenic differentiation. In addition, integrin subunit αv and integrins α6 and α7 were detected at significantly greater levels in ASCs cultured on growth and adipogenic d-ECM, respectively, suggesting that integrins play an important role in ASC migration and adipogenesis. This study demonstrated that stepwise adipogenesis-induced ECM production plays an important role in ASC migration and differentiation. In addition, this study provided a strategy to achieve precise regulation of stem cell function in adipose tissue engineering.